POST-COVID-19 SYNDROME IMAGING FINDINGS IN SEVERE COVID-19 WITH PULMONARY CAVITATION: A CASE REPORT - Soekardi, Adi; Suryamin, Ricky (Faculty of Medicine Universitas Islam Sumatera Utara, 2024)
In the fourth year of the SARS-CoV-2 pandemic, there is corresponding increase in the proportion exhibiting long-term symptoms and chronic respiratory complication associated with the disease. The British Medical Journal consider post-COVID syndrome as to symptoms continuing for more than 12 weeks. The most prevalent findings were